Proses Kreatif Karya Tari Balago Terinspirasi dari Tradisi Parang Pisang di Kabupaten Pesisir Selatan - Syarifa Raudatul Jannah; Emri Emri; Oktavianus Oktavianus; Ali Sukri (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work “Balago”, inspired by the Parang pisang tradition, is one of the cultural heritages of the Minangkabau people found in Batang Kapas Subdistrict, Pesisir Selatan Regency, West Sumatra. This tradition is carried out specifically to welcome the birth of male and female twins, with the purpose of preventing any feelings of affection or romantic love between them as they grow older. The Parang Pisang procession involves two families, namely the Induak Bako family and the family of the twins, through a series of stages such as deliberation, preparation of boiled bananas, a procession featuring si muntu and kudo upie properties, verbal debate, and culminates in a banana war followed by reconciliation and joint prayers. This tradition showcases the uniqueness of local culture through the activity of throwing bananas at each other, which reflects customary communication, togetherness, conflict, and peaceful conflict resolution. Parang Pisang strongly proves that the Minangkabau community possesses cultural traditions rich in meaning, which are still preserved and practiced from generation to generation until today.